Optimization Of Bushing Production Time In Cnc Turning Process Using Taguchi and Root Cause Analysis (Rca) Method - Achmad Yani; Wiwik Sulistyowati (Procedia of Engineering and Life Science, 2021)
PT. WT is a company engaged in the manufacturing industry. To support the fulfillment of the above production results, this company already has several units of sophisticated CNC machines. However, in the application of this CNC machine, there are still problems when making bushing spare parts that have not been able to meet the very high market demand.This is because within 16 hours of effective work it only produces 120 pcs of bushing spare parts, while in 1 month the demand for bushing spare parts from consumers reaches 2,400 pcs. So that in this study, it is necessary to improve the time and quality of production which is more effective and efficient.The research that has been done with the title "optimization of bushing production time in the cnc turning process using the Taguchi method and root cause analysis (RCA)". The data obtained from the results of research with time parameters that must be achieved with the optimization of the cycle time response produced is 74.03 seconds or decreased by 14.37 seconds from factory standards. While the optimum condition is produced at the RPM condition of 3100; Feed of 0.8 mm / put; and Dept of Cut of 0.7 mm / put. With this implementation, the production of these bushing spare parts can increase by 16.33%. Thus, PT. Weiss Tech will be able to meet the target market demand.